1990
DOI: 10.1002/1097-0142(19900701)66:1<56::aid-cncr2820660112>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of failure after curative resection of pancreatic carcinoma

Abstract: Thirty-six patients underwent curative resection of a primary pancreatic carcinoma from January 1977 to September 1987; 26 had Whipple resections, seven had total pancreatectomies, and three had distal pancreatectomies. Twenty-six patients manifested recurrent disease, four died of intercurrent disease, and six were apparently cured. Median survival was 11.5 months with actuarial survival at 2 and 5 years of 32% and 17%, respectively. Of the eventual recurrences, 19% were local only (pancreatic bed, regional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
173
1
6

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(188 citation statements)
references
References 17 publications
8
173
1
6
Order By: Relevance
“…It has also been reported that high doses of radiotherapy (55 Gy or greater) can improve local control in patients with pancreatic carcinoma, compared with radiotherapy at lower doses. 17 5-FU is used as a standard agent for chemoradiotherapy. When 5-FU is administered by bolus injection, it is essentially cleared from plasma in 1 hour.…”
mentioning
confidence: 99%
“…It has also been reported that high doses of radiotherapy (55 Gy or greater) can improve local control in patients with pancreatic carcinoma, compared with radiotherapy at lower doses. 17 5-FU is used as a standard agent for chemoradiotherapy. When 5-FU is administered by bolus injection, it is essentially cleared from plasma in 1 hour.…”
mentioning
confidence: 99%
“…2 Extended surgical resection, intensive chemotherapy, radiation therapy, or a combination of all 3 have been advocated in recent years, but none have prolonged patient survival significantly. New therapy for pancreatic cancer is needed.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The ability of tumor cells to degrade adjacent extracellular matrix is considered an essential step in the processes of invasion and metastasis. 3,4 Matrix metalloproteinases (MMPs) are a family of structurally related zymogens capable of degrading extracellular matrix, including basement membrane.…”
mentioning
confidence: 99%
“…After 3 days, animals were killed and the livers were fixed with 2% formaldehyde in PBS (4°C). Tissues were cut evenly into three slices and incubated in a PBS solution containing 5 mm K 3 Fe(CN) 5 , 5 mm K 4 Fe(CN) 5 , 2 mm MgCl 2 , and 1 mg/ml of X-gal for 18 h at 37°C. 29 After staining, tissues were embedded in paraffin, sectioned, adhered to glass slides, and counter stained with hematoxylin and eosin.…”
Section: Liver Metastasis Modelmentioning
confidence: 99%
“…[1][2][3][4][5][6] In particular, liver metastasis frequently occurs (about 60%) after a surgical resection for pancreatic adenocarcinoma even if it is performed with a curative intent. 5 No effective therapeutic modality has been established to prevent liver metastasis or to treat it successfully. In human pancreatic cancer, point mutation of the c-K-ras protooncogene at codon 12/13 is frequently detected.…”
Section: Introductionmentioning
confidence: 99%